Istifham in surah al-a'raf (dirasatun tahliliyyatun balaghiyyatun) - Nurjannah, Nurjannah; Nur Fadhila; Agussalim Beddu Malia (Jurnal Info Sains : Informatika dan Sains, 2024)
Istifham contains two meanings, namely the essential meaning and the majazi meaning. The true meaning of istifham is to question something that we do not yet know with the adawat of istifham. Meanwhile, the meaning of majazi is used for something that is outside the true meaning of istifham. Insya talabi specifically chose the form of istifham, because in the concept of ma'ani science, istifham does not always take the form of a direct question in a conversation, sometimes there is a deviation in meaning from the original meaning to a meaning that is out of the original meaning. The urgency of this research is so that readers can understand the contents of the Qur'an which contains istifham (question sentences) and to find out the diversity of meanings of istifham contained in Surah Al-A'raf. The method used is a qualitative descriptive method by analyzing the use of istifham in Surah Al-A'raf. Based on data obtained from Surah Al-A'raf regarding istifham adat from 206 verses in Surah Al-A'raf there are 9 forms of Istifham adat in 47 verses .The meaning of Balaghah contained in it is: Al-Inkar 24 verses, At-taqrir 5 verses, At-taubih 10 verses, An-nafi 4 verses, At-tahsir 1 verse, At-tamanni 1 verse, At-tahkir 1 verse, At-ta'zhim 1 verse, Al-Makhzufakh 1 verse and At-taswiyyah 1 verse.